TET3 overexpression facilitates DNA reprogramming and early development of bovine SCNT embryos. Issue 3 (September 2020) - Zhang, Jian; Hao, Linlin; Wei, Qian; Zhang, Sheng; Cheng, Hui; Zhai, Yanhui; Jiang, Yu; An, Xinglan; Li, Ziyi; Zhang, Xueming; Tang, Bo
Abstract : Somatic cell nuclear transfer (SCNT) has been successfully used for cloning in a variety of mammalian species. However, SCNT reprogramming efficiency is relatively low, in part, due to incomplete DNA methylation reprogramming of donor cell nuclei. We previously showed that ten-eleven translocation 3 ( TET3 ) is responsible for active DNA demethylation during preimplantation embryonic development in bovines. In this study, we constructed TET3 -overexpressing cell lines in vitro and observed that the use of these fibroblasts as donor cells increased the blastocyst rate by approximately 18 percentage points compared to SCNT. The overexpression of TET3 in bovine SCNT embryos caused a decrease in the global DNA methylation level of the pluripotency genes Nanog and Oct-4, ultimately resulting in an increase in the transcriptional activity of these pluripotency genes. Moreover, the quality of bovine TET3-NT embryos at the blastocyst stage was significantly improved, and bovine TET3-NT blastocysts possessed more total number of cells and fewer apoptotic cells than the SCNT blastocysts, similar to in vitro fertilization (IVF) embryos. Nevertheless, DNA methylation of the imprinting control region (ICR) for the imprinted genes H19 - IGF2 in SCNT embryos remained unaffected by TET3 overexpression, maintaining parent-specific activity for further development. Thus, the results of our study provide a promising approach to rectify incomplete epigenetic reprogramming and achieve higher cloning efficiency.